2021
DOI: 10.1088/1757-899x/1096/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Design of Hug Machine Portable Seat for Autistic Children in Public Transport Application

Abstract: The prevalence of autism in Indonesia was estimated approximately 2.5 million people. There are at least 500 new cases was diagnosed annually. Self-injurious behaviour is one of the most prevalence in autistic children. Only a few studies had been done in Indonesia regarding autism issue. Therefore, this study aims to design a hug machine portable seat for autistic children, called Autism Hug Machine Portable Seat (AHMPS), which can be used in public transportation (bus and train) to provide safety and for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Two models of an AHMPS designed from a previous study were used: an AHMPS with an inflatable wrap and an AHMPS with a manual strap as shown in Figure 1 [ 34 ]. The pressure load was determined based on a qualitative comfort test in 15 adult healthy and asymptomatic individuals, conducted in a previous study [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two models of an AHMPS designed from a previous study were used: an AHMPS with an inflatable wrap and an AHMPS with a manual strap as shown in Figure 1 [ 34 ]. The pressure load was determined based on a qualitative comfort test in 15 adult healthy and asymptomatic individuals, conducted in a previous study [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…AHMPS manual pull and inflatable wrap models invented in the previous study were used [19]. The AHMPS manual pull is a portable seat with foam straps in the chest and thigh that can press the user's body when straps are pulled like a safety belt.…”
Section: Hug Machinementioning
confidence: 99%
“…Yonkman [18] reported that children with ASD would become aggressive and show self-injurious behavior when traveling in a vehicle. Afif [19] then designed the Hug Machine Portable Seat to provide a deep pressure effect and be used in public vehicles. However, this tool has not been tested experimentally.…”
Section: Introductionmentioning
confidence: 99%